Electronics explained fundamentals for engineers, technicians, and makers - Frenzel, Louis E. Jr. 1938- (Newnes, 2018)
Electronics Explained, Second Edition, takes a systems based approach to the fundamentals of electronics, covering the different types of electronic circuits, how they work, and how they fit together to create modern electronic equipment, enabling you to apply, use, select, operate and discuss common electronic products and systems.--Provided by publisher.